-7v+4(v-6)=6

Simple and best practice solution for -7v+4(v-6)=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7v+4(v-6)=6 equation:



-7v+4(v-6)=6
We move all terms to the left:
-7v+4(v-6)-(6)=0
We multiply parentheses
-7v+4v-24-6=0
We add all the numbers together, and all the variables
-3v-30=0
We move all terms containing v to the left, all other terms to the right
-3v=30
v=30/-3
v=-10

See similar equations:

| 3x-5x=10+2 | | 10(2n+3)=130 | | (2k÷5)-(4k÷9)=-2 | | 4w+8(w+7)=8 | | 14-13s=12 | | 6(y-6)+2y=28 | | 4x+16+2x+34=180 | | -42-6x=-12 | | 4x+16-3=7 | | 2x=15.7 | | 149-51=x | | 4x+4-3=7 | | 2x(3-x)=4 | | 24x=122 | | 150-111=x | | (2K÷5)一(4k÷9)=一2 | | 1/2x+1.5=6.5 | | 2k–6=4 | | R-8=6r+6 | | 4(x+4)-3=7 | | x+33/5=41/3 | | 4(x+16)-3=7 | | 3/4x-1=-1/2x+9 | | -30+4x=-45 | | (m+1)(m+2)(m+3)/(m=2)(m+1)^2 | | 3x–1=1 | | 6(x+2)–2x+8=16* | | 2k/5-4k/9=-2 | | 1+3a=14+8−8a+8a= | | 6(x+2)–2x+8=16 | | y–12=12 | | 7^x-5=40 |

Equations solver categories